2012
DOI: 10.1016/j.chom.2012.09.002
|View full text |Cite|
|
Sign up to set email alerts
|

Differential Responses of Immune Cells to Type I Interferon Contribute to Host Resistance to Viral Infection

Abstract: Type I interferons (IFNs) are central to antiviral defense, but how they orchestrate immune cell function is incompletely understood. We determined that IFNs produced during murine cytomegalovirus (MCMV) infection differentially affect dendritic cells (DCs) and natural killer (NK) cells. IFNs induce cell-intrinsic responses in DCs, activating antiproliferative, antiviral, and lymphocyte-activating gene networks, consistent with high activity of the transcription factor STAT1 in these cells. By comparison, NK c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
110
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 90 publications
(120 citation statements)
references
References 22 publications
9
110
1
Order By: Relevance
“…It was previously reported that the TFs Blimp1 and Ets1 negatively regulate NKC proliferation in response to IL-15 (53,58), while the ETS TF-family member Pu.1 positively regulates the proliferative response to IL-2 (51). More recently, members of the E2F TF family known to control the cell cycle were implicated in NKC IL-15 signaling (67). Only a few Runx3 target genes were identified using NK cell lines (37,69), and no information is available about the Runx3-mediated transcriptional program regulating the NKC response to IL-15.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously reported that the TFs Blimp1 and Ets1 negatively regulate NKC proliferation in response to IL-15 (53,58), while the ETS TF-family member Pu.1 positively regulates the proliferative response to IL-2 (51). More recently, members of the E2F TF family known to control the cell cycle were implicated in NKC IL-15 signaling (67). Only a few Runx3 target genes were identified using NK cell lines (37,69), and no information is available about the Runx3-mediated transcriptional program regulating the NKC response to IL-15.…”
Section: Discussionmentioning
confidence: 99%
“…Conditional KO mice lacking expression of Runx3 only in NKC could certainly support the conclusion of Runx3 cell-autonomous function in NKC. However, our attempts to use Runx3 (67). In this regard, it is of interest to note that Runx3 was recently identified as one of the sustained effector genes induced in murine cytomegalovirus (MCMV)-infected Ly49H ϩ NKC during clonal expansion (61).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on mouse CMV (MCMV) infection have shown that cytokines like type I IFNs are secreted upon virus challenge, and this response regulates the NK-cell response [29]. Thus, we tested whether type I IFNs were involved in hcmv-miR-UL112-induced NK cell cytotoxicity regulation.…”
Section: Hcmv-mir-ul112 Reduced the Cd107-expression On Nk Cells By Imentioning
confidence: 97%
“…Many studies have shown that type I IFNs can directly activate NK cells [32][33][34]; however counterevidence argues that a direct action of type I IFNs is not necessarily required to efficiently activate NK cells [35][36][37].…”
Section: Type I Ifn-mediated Direct and Indirect Mechanisms Of Actionmentioning
confidence: 98%